Perlindungan Konsumen atas Penjualan Produk Pakaian Obral Tanpa Informasi yang Lengkap Melalui Media Online pada Masa Pandemi Covid-19 - I Kadek Bagiasa; I Nyoman Putu Budiartha; Ni Gusti Ketut Sri Astiti (Warmadewa Press, 2022)
The existence of affordable products, on the one hand, is useful for the parties, but there are hidden conditions related to trade in goods marketed at very low prices that are not really beneficial to consumers. The purposes of this study are to reveal the protection of consumers who are harmed by not providing complete information about clothing products on sale through online media and the responsibility of business actors for consumer losses who receive incomplete information. This type of research uses a normative legal research type. Normative legal research with a statutory approach. Sources of legal materials used are primary and secondary legal sources. In order to collect primary and secondary legal materials using an inventory technique and presented in a descriptive form. The results of the study reveal that the provision of consumer legal protection for incomplete information on goods can be divided into preventive legal protection and also repressive legal protection. The responsibility of the seller of the goods to compensate for the loss, whether in the form of a refund, exchange of the same goods or having a comparable nominal. The compensation must be carried out within seven days of the transaction being executed. If it is found at a later date that there is more evidence of wrongdoing regarding the loss suffered by the consumer, so that the compensation paid by the seller of the goods does not rule out the possibility of criminal prosecution. However, the seller of the goods may be relieved of the responsibility to provide such compensation.